IMPLEMENTASI E-GOVERNMENT DALAM PEMERINTAHAN KECAMATAN SEDAYU “SEDAYU SMART DISTRIC” - Ardiyati (Halu Oleo University, 2022)
The research have a purpose to analyze the implementation of e-government policies in Sedayu District government in the concept of